Galectin-1 sensitizes resting human T lymphocytes to Fas (CD95)-mediated cell death via mitochondrial hyperpolarization, budding, and fission. - Matarrese, Paola (2005)
Galectins have emerged as a novel family of immunoregulatory proteins implicated in T cell homeostasis. Recent studies showed that galectin-1 (Gal-1) plays a key role in tumor-immune escape by killing antitumor effector T cells. Here we found that Gal-1 sensitizes human resting T cells to Fas (CD95)/caspase-8-mediated cell death. Furthermore, this protein triggers an apoptotic program involving an increase of mitochondrial membrane potential and participation of the ceramide pathway. In addition, Gal-1 induces mitochondrial coalescence, budding, and fission accompanied by an increase and/or redistribution of fission-associated molecules h-Fis and DRP-1. Importantly, these changes are detected in both resting and activated human T cells, suggesting that Gal-1-induced cell death might become an excellent model to analyze the morphogenetic changes of mitochondria during the execution of cell death. This is the first association among Gal-1, Fas/Fas ligand-mediated cell death, and the mitochondrial pathway, providing a rational basis for the immunoregulatory properties of Gal-1 in experimental models of chronic inflammation and cancer.